Direct balancing of lipid mobilization and reactive oxygen species production by the epoxidation of fatty acid catalyzed by a cytochrome P450 protein during seed germination. Issue 6 (27th December 2022) - Xiang, Fuyou; Liu, Wen‐Cheng; Liu, Xin; Song, Yuwei; Zhang, Yu; Zhu, Xiaojing; Wang, Pengtao; Guo, Siyi; Song, Chun‐Peng
Summary: Fatty acid (FA) β‐oxidation provides energy for oil seed germination but also produces massive byproduct reactive oxygen species (ROS), posing potential oxidative damage to plant cells. How plants overcome the contradiction between energy supply and ROS production during seed germination remains unclear. In this study, we identified an Arabidopsis mvs1 (methylviologen‐sensitive) mutant that was hypersensitive to ROS and caused by a missense mutation (G1349 substituted as A) of a cytochrome P450 gene, CYP77A4 . CYP77A4 was highly expressed in germinating seedling cotyledons, and its protein is localized in the endoplasmic reticulum. As CYP77A4 catalyzes the epoxidation of unsaturated FA, disruption of CYP77A4 resulted in increased unsaturated FA abundance and over accumulated ROS in the mvs1 mutant. Consistently, scavenging excess ROS or blocking FA β‐oxidation could repress the ROS overaccumulation and hypersensitivity in the mvs1 mutant. Furthermore, H2 O2 transcriptionally upregulated CYP77A4 expression and post‐translationally modified CYP77A4 by sulfenylating its Cysteine‐456, which is necessary for CYP77A4's role in modulating FA abundance and ROS production. Together, our study illustrates that CYP77A4 mediates direct balancing of lipid mobilization and ROS production by the epoxidation of FA during seed germination.